Causal Factors Affecting the Audit Quality of The Thai Certified Public Accountants - Rattanasing, Nutrada; Sanpakdee, Pitan; Kookkaew, Pathompong (Arts of Management Journal, 2024)
This research article aims to 1) investigate the coherence of the causal relationship model of Thai-certified public accountants' audit quality and 2) study the direct and indirect effects on the audit quality of Thai-certified public accountants. Three hundred twenty qualified public accountants in Thailand who wished to share contact details with the Accounting Profession Council under royal patronage made up the sample group for the study. This study used a mixed method. The data analysis employed descriptive and inferential statistics and the structural equation model (SEM). The research results were as follows: 1) The causal relationship model of Thai certified public accountants' audit quality was highly consistent with the actual data, suggesting that auditor independence, auditor competency, and professional skepticism can explain 38% of the variance in audit quality. 2) Auditor independence has a positive direct effect on audit quality and professional skepticism and indirectly enhances audit quality through professional skepticism. Auditor competency positively impacts professional skepticism but does not directly affect audit quality. However, professional skepticism has a positive indirect effect on audit quality.